Bilingual First Language Acquisition: Evidence from Montreal - Genesee, Fred (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2008)
AbstractBilingual code-mixing is the use of elements (phonological, lexical, and morpho-syntactic) from two languages in the same utterance or stretch of conversation or in different situations. Bilingual code-mixing is ubiquitous among bilinguals, both child and adult. Child bilingual code-mixing has been interpreted by researchers and laypersons as an indication of linguistic confusion and incompetence. This article reviews a series of studies on French-English simultaneous bilinguals from Montreal that examined their code-mixing with respect to young bilingual children’s ability: to differentiate their developing languages, to control code-mixing in different communicative situations, to adjust their code-mixing in response to feedback from interlocutors, and to fill gaps in their developing language competence. Contrary those who view child code-mixing as evidence of confusion and incompetence, extant evidence indicates that it reflects linguistic and communicative competence even in very early stages of simultaneous bilingual acquisition.